2011
DOI: 10.1111/j.1468-2494.2010.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

A new potent natural antioxidant mixture provides global protection against oxidative skin cell damage

Abstract: Oxidative stress occurs when there is an over production of free radicals and cells are not able to neutralize them by their own antioxidant mechanisms. These excess of free radicals will attack cellular macromolecules leading to cell damage, function impairment or death. Because of that, antioxidant substances have been largely used in products to offer complementary protection. In this study a new mixture of three known antioxidants (cocoa, green tea and alpha-tocopherol) was evaluated and its antioxidant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This suggested that S. oleraceus extracts can not only assist cells to recover from acute H 2 O 2 stress, but can also protect cells from chronic stress applied for five consecutive days as tested in the present study. Similar to the present results, a mixture of cocoa and green tea extracts, rich in polyphenols, and vitamin E significantly reduced UV stress-induced premature senescence from 51.67% to 38.81% in human dermal fibroblasts [46]. Oxidative DNA damage has been demonstrated to be proportional to the age of WI-38 human fibroblast cells [9] and was proposed to be another biomarker for cellular senescence.…”
Section: Resultssupporting
confidence: 82%
“…This suggested that S. oleraceus extracts can not only assist cells to recover from acute H 2 O 2 stress, but can also protect cells from chronic stress applied for five consecutive days as tested in the present study. Similar to the present results, a mixture of cocoa and green tea extracts, rich in polyphenols, and vitamin E significantly reduced UV stress-induced premature senescence from 51.67% to 38.81% in human dermal fibroblasts [46]. Oxidative DNA damage has been demonstrated to be proportional to the age of WI-38 human fibroblast cells [9] and was proposed to be another biomarker for cellular senescence.…”
Section: Resultssupporting
confidence: 82%
“…To explore the mechanism in detail, we checked the state of intracellular molecules such as lipids, protein, and DNA, which play various important roles in the cells [31]. Furthermore, intracellular macromolecular damage can be recognized as oxidative stress [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antioxidant-rich sources and supplements are under the spotlight to offer extra protection. Although many chemical substances have been proved for their antioxidant activity, there has been a continuous search for new antioxidants from natural sources because of the poor bioavailability, cumulative effects inside the body, and adverse side effects of synthetic substances (Jorge et al 2011 ). Many researches among ascidians tunics showed their strong antioxidant effects and they have similar or higher defense activity as the raw contents of ascidians (Table 27. 6 , Jo et al 2010 ;Kim et al 2005 ;Nacional et al 2011 ;Park et al 2010 ).…”
Section: Antioxidantsmentioning
confidence: 99%